A Business Proposal: A Study of Netizens' Perceptions of the Cancel Culture Phenomenon in the Film Industry - Sarifhatul Aini Yuliyus Putri; Siti Khumayah; Aghnia Dian Lestari (Al-Makki Publisher, 2026)
Social media has become a digital public sphere that plays a significant role in shaping public opinion and social sanctions against public figures. One emerging phenomenon is